FIGURATIVE LANGUAGE IN SONG LYRICS OF ELOISE’S SELECTED SONGS - Ni Km. Nidyantari Laksmi R.; I Nyoman Aryawibawa; I Nengah Sudipa (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2023)
Figurative Language in Song Lyrics of Eloise’s Selected Songs aims at identifying the kinds of figurative language and explaining the meaning of figurative language implied in song lyrics of each song. Some selected songs from Eloise are the data of this undergraduate thesis, especially from the album This Thing Called Living and Somewhere In-Between. There are five songs selected as the data to identify, they are Subside, TTCL, Intertwined, Wanderlust, and Hungover. In order to collect the data, documentation and note-taking technique were applied in this study. Also, descriptive qualitative was used to analyse the song. Hence, informal method was presented to be a method of presenting the whole data. A theory of figurative language proposed by Knicerbocker & Reninger (1963) to identify the first problem and a theory of meanings proposed by Leech (1983) to explain the second problem in this study. As the result, this undergraduate thesis identified that there are seven kinds of figurative language found in the song lyrics namely simile, metaphor, personification, synecdoche, metonymy, hyperbole, and irony. Moreover, there are four types of meaning found, they are conceptual meaning, connotative meaning, stylistic meaning, and affective meaning.